A Case Study on Ek-Kustha (Psoriasis) Ayurvedic Management (AYUSHDHARA, 2024)
In present era, skin diseases have become a major hazard for mental health more than physical, as it disturbs the cosmetic harmony. Psoriasis is marked by periodic flare-ups of sharply defined red patches, covered by a silvery, flaky surface. The Ayurvedic finding is considered as Ek Kustha which is a Vata- Kapha transcendent Kshudra Kushtha. Here, an effort was made to treat a female patient suffering from pustular psoriasis through Ayurved as the eminent choice. Since the treatment of wide range of Kustha is Sanshodhana alongside Sanshamana drugs but in this case, at first, Lepa karma and Shamana Aushadhi was performed. After Lepa Karma, Sanshamana drugs were given for 30 days. This case report showed that consolidated Ayurvedic modalities brought about extraordinary improvement in the condition of patient.